2017
DOI: 10.1038/am.2017.95
|View full text |Cite
|
Sign up to set email alerts
|

Formation of resonant bonding during growth of ultrathin GeTe films

Abstract: A highly unconventional growth scenario is reported upon deposition of GeTe films on the hydrogen passivated Si(111) surface. Initially, an amorphous film forms for growth parameters that should yield a crystalline material. The entire amorphous film then crystallizes once a critical thickness of four GeTe bilayers is reached, subsequently following the GeTe(111) || Si(111): GeTe [−110] || Si[−110] epitaxial relationship rigorously. Hence, in striking contrast to conventional lattice-matched epitaxial systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 42 publications
1
50
0
Order By: Relevance
“…[ 72 ] In contrast, when GeTe is grown using the same conditions on the Si(111)–(√3 × √3)R30°–Sb surface, even at lower temperatures like 230 °C, it directly grows with a crystalline structure. [ 72 ] When the GeTe film is grown beyond four BLs on the Si(111)–(1 × 1)–H surface it switched to an epitaxial structure (for the entire film). The observed behavior can be well explained by (de)stabilizing effects of MVB, where, e.g., above a critical thickness a transition from localized covalent bonding in the amorphous phase to MVB in the crystalline phase is observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 72 ] In contrast, when GeTe is grown using the same conditions on the Si(111)–(√3 × √3)R30°–Sb surface, even at lower temperatures like 230 °C, it directly grows with a crystalline structure. [ 72 ] When the GeTe film is grown beyond four BLs on the Si(111)–(1 × 1)–H surface it switched to an epitaxial structure (for the entire film). The observed behavior can be well explained by (de)stabilizing effects of MVB, where, e.g., above a critical thickness a transition from localized covalent bonding in the amorphous phase to MVB in the crystalline phase is observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, ultrathin films of GeTe grown by molecular beam epitaxy (MBE) on a Si(111)–(1 × 1)–H substrate surface at a temperature as high as 260 °C, well above the crystallization temperature of bulk GeTe of 200 °C, turn out to be initially (up to four bilayers (BLs)) amorphous. [ 72 ] In contrast, when GeTe is grown using the same conditions on the Si(111)–(√3 × √3)R30°–Sb surface it directly grows with a crystalline structure. [ 72 ] When the GeTe film is grown beyond four BLs on the Si(111)–(1 × 1)–H surface it switches to an epitaxial structure (for the entire film).…”
Section: Introducing a New Bonding Mechanism: Metavalent Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to thermal annealing, pressure [85,107,108,109,110,111], strain [112,113], chemical composition [14,16], ion bombardment [114], focused electron beam irradiation [92], electric field [115,116], voltage pulses [117,118,119], laser and photonic excitation [120,121], and interface template [93,122,123] are shown to be effective approaches in tuning disorder in GST and related compounds. It is also worth mentioning that the remaining disorder in ultrathin hexagonal GST films ~7–14 nm would result in a weak anti-localization phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also observed this transition for the growth of GeTe on Si(1 1 1)-7 × 7, [49] but not for the growth of GeTe on Si(1 1 1)-√3 × √3-Sb [50], which is consistent with this picture. Wang et al related this transition to the different types of bonding present in conventional semiconductors, such as GaSb and Si, and PCM, such as GST [51].…”
Section: (0 0 1)-oriented Substratesmentioning
confidence: 99%